2013
DOI: 10.1371/journal.pone.0073641
|View full text |Cite
|
Sign up to set email alerts
|

Human APOBEC3A Isoforms Translocate to the Nucleus and Induce DNA Double Strand Breaks Leading to Cell Stress and Death

Abstract: Human APOBEC3 enzymes deaminate single stranded DNA. At least five can deaminate mitochondrial DNA in the cytoplasm, while three can deaminate viral DNA in the nucleus. However, only one, APOBEC3A, can hypermutate genomic DNA. We analysed the distribution and function of the two APOBEC3A isoforms p1 and p2 in transfected cell lines. Both can translocate to the nucleus and hypermutate CMYC DNA and induce DNA double strand breaks as visualized by the detection of ©H2AX or Chk2. APOBEC3A induced G1 phase cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 117 publications
8
98
2
Order By: Relevance
“…4D) (32, 54). Suspene et al and Mussil et al (39,54) demonstrated that A3A hypermutates host nuclear gene loci such as TP53 and c-myc in activated T cells and UGI-expressing 293T cells. Because robust E2 hypermutation was detected in the A3A-and UGI-expressing W12 cells (Fig.…”
Section: Induction Of Apobec3 Genes By Ifn-␤ Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…4D) (32, 54). Suspene et al and Mussil et al (39,54) demonstrated that A3A hypermutates host nuclear gene loci such as TP53 and c-myc in activated T cells and UGI-expressing 293T cells. Because robust E2 hypermutation was detected in the A3A-and UGI-expressing W12 cells (Fig.…”
Section: Induction Of Apobec3 Genes By Ifn-␤ Stimulationmentioning
confidence: 99%
“…We analogously speculate that uracil bases in the E2 gene generated by A3s may result in DNA strand breaks, leading to viral DNA integration. Moreover, it was recently reported that A3A and A3B expression induces DNA double-strand breaks and genomic instability (13,54,56). DNA strand breaks in viral DNA and host genomic DNA may synergistically increase the chance of viral DNA integration.…”
Section: Induction Of Apobec3 Genes By Ifn-␤ Stimulationmentioning
confidence: 99%
“…Thus, the potential exists for these proteins to deaminate cytidine residues of chromosomal DNA. The overexpression of A3A in cultured cells has been shown by some investigators to result in mutation of both nuclear and mitochondrial DNA (Landry et al, 2011;Suspène et al, 2011a;Aynaud et al, 2012;Lackey et al, 2013;Mussil et al, 2013). Moreover, ecotopic expression of A3A in HEK293 cells is generally toxic to cells.…”
Section: Dna Damage and A3amentioning
confidence: 99%
“…A3A notably is able to hypermutate nuclear DNA (nuDNA) resulting in the formation of double-stranded DNA breaks (DSBs) and apoptosis [2][3][4] . In addition, A3A could deaminate DNA molecules harbouring a variety of 5-oxidized cytidine bases including 5-methylcytidine (5Me-dC; refs 5-7).…”
mentioning
confidence: 99%